Lung ventilation‐ and perfusion‐weighted Fourier decomposition magnetic resonance imaging: In vivo validation with hyperpolarized 3He and dynamic contrast‐enhanced MRI. Issue 1 (5th March 2012) - Bauman, Grzegorz; Scholz, Alexander; Rivoire, Julien; Terekhov, Maxim; Friedrich, Janet; de Oliveira, Andre; Semmler, Wolfhard; Schreiber, Laura Maria; Puderbach, Michael
Abstract The purpose of this work was to validate ventilation‐weighted (VW) and perfusion‐weighted (QW) Fourier decomposition (FD) magnetic resonance imaging (MRI) with hyperpolarized 3He MRI and dynamic contrast‐enhanced perfusion (DCE) MRI in a controlled animal experiment. Three healthy pigs were studied on 1.5‐T MR scanner. For FD MRI, the VW and QW images were obtained by postprocessing of time‐resolved lung image sets. DCE acquisitions were performed immediately after contrast agent injection. 3He MRI data were acquired following the administration of hyperpolarized helium and nitrogen mixture. After baseline MR scans, pulmonary embolism was artificially produced. FD MRI and DCE MRI perfusion measurements were repeated. Subsequently, atelectasis and air trapping were induced, which followed with FD MRI and 3He MRI ventilation measurements. Distributions of signal intensities in healthy and pathologic lung tissue were compared by statistical analysis. Images acquired using FD, 3He, and DCE MRI in all animals before the interventional procedure showed homogeneous ventilation and perfusion. Functional defects were detected by all MRI techniques at identical anatomical locations. Signal intensity in VW and QW images was significantly lower in pathological than in healthy lung parenchyma. The study has shown usefulness of FD MRI as an alternative, noninvasive, and easily implementable technique for the assessment of acute changes in lung function. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.